2009
DOI: 10.1167/iovs.09-3871
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Ocular Anterior Chamber Tissues to Oxidative Damage and Its Relevance to the Pathogenesis of Glaucoma

Abstract: Because the cornea and iris are directly exposed to light, they possess antioxidant defense mechanisms that are not activated in the trabecular meshwork. The peculiar sensitivity of the trabecular meshwork to oxidative stress is consistent with the damage selectively induced in it, triggering glaucoma's pathogenic cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 56 publications
2
95
0
1
Order By: Relevance
“…This issue is relevant because we recently demonstrated that TM is the most sensitive tissue to in vitro oxidative stress in the anterior chamber. 13 The quantification of mtDNA 4977 was carried out by quantitative polymerase chain reaction (QPCR), which is highly sensitive and reliable as confirmed by the increasing number of articles using this method. 14,15 Insofar, evidence demonstrating the purported role of mitochondrial damage in POAG pathogenesis is overwhelming, but most results were not obtained using POAG target tissue, ie, the TM.…”
Section: He Trabecular Meshworkmentioning
confidence: 98%
“…This issue is relevant because we recently demonstrated that TM is the most sensitive tissue to in vitro oxidative stress in the anterior chamber. 13 The quantification of mtDNA 4977 was carried out by quantitative polymerase chain reaction (QPCR), which is highly sensitive and reliable as confirmed by the increasing number of articles using this method. 14,15 Insofar, evidence demonstrating the purported role of mitochondrial damage in POAG pathogenesis is overwhelming, but most results were not obtained using POAG target tissue, ie, the TM.…”
Section: He Trabecular Meshworkmentioning
confidence: 98%
“…Recent reports that vitrectomy and cataract surgery can increase oxygen delivery to the outflow pathway and directly increases oxidative stress (Chang, 2006;Luk et al, 2009;Siegfried et al, 2010). Oxidative stress may also present an important pathogenic step in primary open-angle glaucoma by inducing human trabecular meshwork degeneration, favouring an intraocular pressure (IOP) increase, thus priming the glaucoma pathogenic cascade (Izzotti et al, 2009;Sacca et al, 2005). The iris microvasculature being the predominant source of oxygen in the region most likely plays a critical role in maintaining oxygen homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports that intraocular surgery can disturb the intraocular oxygen gradients, increase oxygen delivery to the outflow pathway and directly induce oxidative stress (Chang, 2006;Luk et al, 2009;Siegfried et al, 2010). Oxidative stress may also present an important pathogenic step in primary open-angle glaucoma by inducing trabecular meshwork degeneration, favouring an intraocular pressure (IOP) increase, thus priming the glaucoma pathogenic cascade (Izzotti et al, 2009;Sacca et al, 2005). Hence, any iris vascular abnormality would probably affect the Fig.…”
Section: Discussionmentioning
confidence: 99%